Effectiveness of Cognitive Behavior Therapy on the Quality of Sleep in Elderly People With Insomnia Disorder - Reza Mottaghi; Ali Kamkar; Alireza Maredpoor (University of Social Welfare & Rehabilitation Sciences, 2016)
Objectives: Taking into consideration the high prevalence of insomnia disorder in the elderly population, this study aims to examine the effectiveness of cognitive behavioral therapy (CBT) in improving the overall quality of sleep and the subscales of sleep quality in the elderly. Methods & Materials: The present study employs experimental research design including 5000 elderly participants from the Jahandedehgan center in Shiraz, Iran. Based on the inclusion and exclusion criteria, a total of 44 subjects were selected randomly. After losing 7.85 percent of the participants, 39 subjects with the mean age of 68 years who were suffering from primary insomnia disorder were evaluated with Pittsburgh Sleep Quality Index (PSQI) in addition to pretest, posttest, and follow-up tests. The intervention took place twice a week within a period of four weeks employing cognitive behavioral therapy based on the ESPIE commands. The SPSS 21 statistical software and covariance of single and multivariate analysis including (ANCOVA and MANCOVA) were used to analyze the collected data. Results: The mean of the overall quality of sleep before and after the intervention in the experimental and control groups were reported to be 12.95 and 12.7, respectively, that later changed to 10.03 and 13.07 in the post-test, and 9.51 and 13.36 during the follow up after three months. From the statistical point of view, the mean of the overall quality of sleep after the intervention was noted to be significant at P<0.001. Conclusion: The present study showed that the cognitive behavioral therapy can enhance the overall quality of sleep and reduce the symptoms of insomnia disorder in the elderly people.